From face to face : recarving of Roman portraits and the Late-Antique portrait arts - Prusac, Marina. (Monumenta Graeca et Romana, 2016)
This book is based on an investigation of more than five hundred recarved portraits. It includes analyses of different recarving methods, some of which can be attributed to geographically localised workshops. The different recarving methods have made it possible to suggest classifiable categories, which together underpin a hypothesis that the late-antique portrait style is a consequence of the many recarved portraits at the time. The practice of portrait recarving emerged due to economic, political, religious and ideological factors, and was influenced by the cultural-historical changes of Late Antiquity. The conclusion gives a new understanding of how wide-ranging, culturally and politically encoded and comprehensive the practice of recarving was.